2019
DOI: 10.1111/ijac.13336
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping and changing of the annealing temperature on the structural and optical properties of ZnS

Abstract: Nano ZnS doped with Co, Mn, or Fe have been synthesized via thermolysis technique at different annealing temperatures (300, 400, and 500°C). The effect of doping and annealing temperature on the lattice parameter and crystalline size of ZnS are studied in detail by Rietveld refinement method of X‐ray diffraction data. To confirm the formation of a zinc blend structure of annealed and doped ZnS, Fourier‐transform infrared are investigated. The energy gaps of doped and annealed ZnS are determined using ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 52 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…It was found that the optical band gap of nano ZnS/Co or ZnS/Mn was first increased then decreased as the annealing temperature increased while in the case of ZnS/Fe, the optical band gap increased as the annealing temperature increased. Furthermore, the emission spectra were affected by the kind of dopant and the annealing temperature of the host matrix [22]. Furthermore, PVA/CMC/PVP polymer blends loaded with ZnS/Co (400 and 500 • C) showed the highest values for the refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the optical band gap of nano ZnS/Co or ZnS/Mn was first increased then decreased as the annealing temperature increased while in the case of ZnS/Fe, the optical band gap increased as the annealing temperature increased. Furthermore, the emission spectra were affected by the kind of dopant and the annealing temperature of the host matrix [22]. Furthermore, PVA/CMC/PVP polymer blends loaded with ZnS/Co (400 and 500 • C) showed the highest values for the refractive index.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the zinc sulfide nanopowder diffraction peaks appeared at 2 θ = 28.63°, 47.39°, and 56.17° denoted (111), (220), and (311) planes for cubic zinc phase (JCPDS Card no. 79‐2204) 45 …”
Section: Resultsmentioning
confidence: 99%
“…79-2204). 45 The average nanofillers crystallite size (D) can be obtained using the Scherrer formula. 46…”
Section: Structural Analysismentioning
confidence: 99%